Digital Vaccination Records: Exploring Stakeholder Perceptions in Gauteng, South Africa - Moonsamy, Wesley; Singh, Shawren (LINK Centre, University of the Witwatersrand (Wits), Johannesburg, 2022)
Electronic health (eHealth) is one of the focus areas of the South African Department of Health (DoH), with the ultimate goal being the development of an electronic health record (EHR) for every citizen. A commonly used subset of eHealth data, vaccination records, is still not yet fully digitised in South Africa. This study aimed to determine the perceptions of key stakeholders (doctors, nurses, parents, and school administrators) about a digital system for vaccination records for minors in South Africa’s Gauteng Province. Using a prototype online, cloud-based vaccine records management system created during the research, called e-Vaccination, quantitative and qualitative interaction-related data from 118 participants was collected using a five-point Likert-scale questionnaire. The questionnaire was based on Lund’s (2001) USE user perception framework, which considers usefulness, satisfaction, ease of use, and ease of learning. This study found that the participants supported the use of the digital vaccine records management system, with an emphasis on five identified factors: user friendliness, graphical design, practicality, user experience, and usability. Accordingly, this article recommends that policymakers and system designers carefully consider these factors in the design and development of South Africa’s digital vaccination records management system.